2021
DOI: 10.1136/bmjopen-2021-053270
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for healthcare services among hypertension patients in China: a discrete choice experiment

Abstract: ObjectivesOur study aimed to support evidence-informed policy-making on patient-centred care by investigating preferences for healthcare services among hypertension patients.DesignWe identified six attributes of healthcare services for a discrete choice experiment (DCE), and applied Bayesian-efficient design with blocking techniques to generate choice sets. After conducting the DCE, we used a mixed logit regression model to investigate patients’ preferences for each attribute and analysed the heterogeneities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It is consistent with that of Zhou and colleagues [ 21 ]. First, the primary purpose of seeking medical service for most outpatients in China is to be cured [ 4 , 14 ]. However, most of them lack medical expertise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is consistent with that of Zhou and colleagues [ 21 ]. First, the primary purpose of seeking medical service for most outpatients in China is to be cured [ 4 , 14 ]. However, most of them lack medical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the SEM also demonstrated that the waiting time for medical services is a relevant factor for outpatient satisfaction, supporting evidence from Ma and colleagues [ 11 ]. This finding could be attributed to a universal phenomenon called “three long one short” (long queues for registration, medical examination, payment, and a short time for diagnosis and treatment) in the tertiary public hospitals in China [ 14 , 39 ]. When the waiting time is longer than expected, the patients may be prone to negative emotions, affecting their satisfaction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consideration of individual preferences is a key element of patient-centred care [ 22 ]. An involvement of individual needs and expectations in care decisions is associated with better engagement, health, and quality of life [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Wan et al (16) found that people's preferences toward primary healthcare closely correlated with their socioeconomic status and health status. Yu et al (17) investigated healthcare services preference among hypertension patients in China found that hypertension patients prefer treatment effect and travel time to healthcare facilities the most. Therefore, there is an evident research gap exists between the current study and previous studies in China, i.e., (1) The existing literature mainly focuses on a specific disease, without concerning different situations, e.g., focusing on the specific disease such as hypertension, without concerning infectious diseases, especially during the COVID-19 epidemic outbreak (2) Most of the existing studies only applied a single model, e.g., only using univariate analysis or logistic regressions; and (3) The key factor of "medical insurance reimbursement ratio" has been .…”
Section: Introductionmentioning
confidence: 99%